Félix-Archimède Pouchet, professeur de sciences naturelles de Flaubert - Maryline Coquidé (Flaubert: Revue Critique et Génétique)
Why did Félix Archimède Pouchet (1800-1872) draw our attention in this Journal’s issue on Gustave Flaubert and Natural Sciences? In the history of science Pouchet is mainly known as Pasteur’s opponent between 1859 and 1864, in the dispute over “spontaneous generation”. Firmly settled in Rouen, Félix Pouchet was in turn: Docteur Achille Flaubert’s pupil at the Hôtel Dieu, founder of the Natural History Museum and Gustave Flaubert’s professor at the Collège Royal. His lesser known research, on human fertility control, and his activities as popularizer constantly involved him in his time. Gustave Flaubert always maintained his admiration and affection for his former professor. After having outlined Félix Pouchet’s origins, and situated the cultural context of his major works in Natural Sciences, I will put these in perspective in Flaubert’s writings.